Effects of Kiwifruit Peel Extract and Its Antioxidant Potential on the Quality Characteristics of Beef Sausage - Evans Frimpong Boateng; Ziyi Yang; Wangang Zhang (MDPI AG, 2022)
In the wake of arresting consumers' health concerns associated with synthetic antioxidants used in meat products, kiwifruit peel by-product was explored as a natural antioxidant source in the current study. A lyophilized kiwifruit peel extract (KPE) at various concentrations of KPE1 (1.5%), KPE2 (3%), and KPE3 (4.5%) was incorporated into formulated beef sausages to compare the physicochemical, sensory quality, and antioxidant efficacy to the treatments of control (CT 0% KPE) and butylated hydroxytoluene (BHT 0.01%) during 12 d of refrigerated (4 ± 1 °C) storage. The KPE inclusion levels induced significantly higher yellowness (b*) values than CT and BHT, whereas no negative influence of KPE was revealed for lightness (L*) and redness (a*). The pH values of the KPE treatments were reduced, and cooking yield increased significantly (p < 0.05), in line with the increasing amount of KPE percentages (1.5%, 3%, and 4.5%) compared to CT and BHT samples. E-nose results showed an enhancement in aroma in KPE treatments, compared to BHT and CT, during the storage period. KPE3 treatment showed a constant lesser value in 2-Thiobarbituric acid reactive substances (TBARS) as storage days increased, compared to the CT and BHT samples. Overall, the KPE is effective for antioxidative capacity, and has the potential to be used as a natural antioxidant in beef sausage.